NEW EXPERIMENT IN KATHAK DANCE: ANALYTICAL STUDY: कत्थक नृत्य में नवीन प्रयोगः विश्लेष्णात्मक अध्ययन - Grover, Bhavna (International Journal of Research -GRANTHAALAYAH, 2015)
Indian classical dance has been a huge and rich tradition since the beginning of Kathak. With the change of time from the beginning, there were new experiments in Kathak dance and dance also changed. By the time of the sixteenth century, which we know as the ritual period, Kathak dance had the influence of Ram and Krishna devotion and Ram and Krishna leelas were the mainstay of Kathak dance. In the seventeenth and eighteenth centuries, when the Kathak dancers received the patronage of the Nawabo and the states and new experiments in Kathak dance resulted in many changes. Kathak was a satvic form of dance for Hindu kings and Muslim Nawabs, who were naturally adorned and luxuries, became adorned here as Kathak. In the nineteenth century, on the basis of style and lineage, three styles of Kathak dance developed as Gharanas, which are known as Jaipur Gharana, Lucknow Gharana and Banaras Gharana. Another obsolete gharana, the Raigad gharana developed under the patronage of Raja Chakradhar Singh of Raigad. Different styles of each household were distinguished according to the region and nature of the kings. Until that time, Kathak was traditionally performed in every household and dances based on mythology were performed as a new experiment. After the development of the dharnas, the main changes came in the side of Kathak. At that time, new uses of Kathak developed such as Salami, Aamad and Thumri, Dadra etc. in acting instead of Pramanam. भारतीय शास्त्रीय नृत्य कथक की आरंभ से ही एक विशाल व समृद्ध परम्परा रही है। प्रारंभ से ही समय परिवर्तन के साथ-साथ कथक नृत्य में नवीन प्रयोग होते रहे और नृत्य परिवर्तित भी होता गया। सोलहवीं शताब्दी जिसे हम रीति-काल के नाम से पहचानते है उस समय तक कथक नृत्य पर राम व कृष्ण भक्ति का प्रभाव था तथा राम व कृष्ण लीलाओं ही कत्थक नृत्य का मुख्य आधार थी। सत्र्ाहवीं व अठारहवीं शताब्दी में जब कथक नर्तको को नवाबो व राज्यों का संरक्षण प्राप्त हुआ और कथक नृत्य में नये प्रयोग हुए फलतः अनेक परिवर्तन आये। हिन्दु राजाओं के यहाँ कथक नृत्य का सात्विक रूप रहा और मुस्लिम नवाबों जो स्वभावतः श्रृंगारप्रिय व विलासिता पूर्ण थे, यहाँ पर कथक का स्वरुप श्रृंगारिक बना। शैली व वंशावली के आधार पर उन्नीसवी सदी में कथक नृत्य की तीन शैलियाँ, घरानों के रूप में विकसित हुई जो जयपुर घराना, लखनऊ घराना व बनारस घराना के रूप में जाने जाते है। एक अन्य अप्रचलित घराना, रायगढ़ घराना जो रायगढ़ के राजा चक्रधर सिंह के संरक्षण में विकसित हुआ। प्रत्येक घराने की भिन्न-भिन्न शैली उस क्षेत्र व राजाओं के स्वभाव के अनुसार प्रतिष्ठित हुई। उस समय तक प्रत्येक घराने में कथक की प्रस्तुति परम्परागत रूप से की जाती थी और पौराणिक कथाओं पर आधारित नृत्य नवीन प्रयोग के रूप में किये जाते थे। धरानों के विकसित होने पर मुख्य परिवर्तन कथक के नृत्त पक्ष में आ गये। उस समय कथक के नवीन प्रयोग विकसित हुए जैसे- प्रणाम के टुकडे के स्थान पर सलामी, आमद व अभिनय में ठुमरी, दादरा आदि का प्रचलन हुआ।